INFLUENCE OF THE BUDGET DEFICIT ON THE IMPLEMENTATION OF THE STATE STABILIZATION POLICY - R. Kalinovskyi (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article reveals the essence of the process of state budget balancing. The key problems connected with the state budget deficit are investigated. The state and dynamics of the Ukraine state budget are considered. The ways of overcoming the consequences of state budget imbalances are analyzed.